An ultra-wideband tunable multi-wavelength Brillouin fibre laser based on a semiconductor optical amplifier and dispersion compensating fibre in a linear cavity configuration - Zulkifli, Mohd Zamani; Ahmad, Harith; Hassan, Nor Ahya; Jemangin, M. H.; Harun, Sulaiman Wadi (Turpion Ltd, 2011)
A multi-wavelength Brillouin fibre laser (MBFL) with an ultra-wideband tuning range from 1420 nm to 1620 nm is demonstrated. The MBFL uses an ultra-wideband semiconductor optical amplifier (SOA) and a dispersion compensating fibre (DCF) as the linear gain medium and nonlinear gain medium, respectively. The proposed MBFL has a wide tuning range covering the short (S-), conventional (C-) and long (L-) bands with a wavelength spacing of 0.08 nm, making it highly suitable for DWDM system applications. The output power of the observed Brillouin Stokes ranges approximately from -5.94 dBm to -0.41 dBm for the S-band, from -4.34 dBm to 0.02 dBm for the C-band and from -2.19 dBm to 0.39 dBm for the L-band. The spacing between each adjacent wavelengths of all the three bands is about 0.08 nm, which is approximately 10.7 GHz for the frequency domain. © 2011 Kvantovaya Elektronika and Turpion Ltd.